2022
DOI: 10.1159/000524366
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated with Impaired Survival after Surgery for Pancreatic Neuroendocrine Tumors

Abstract: Introduction: Pancreatic neuroendocrine tumors (pNETs) are a heterogeneous group of neoplasms. Surgery is the only curative treatment option. However, our understanding of predictors of survival after surgery remains incomplete. The aim of the study was to evaluate metabolic syndrome (MetS) as a prognostic factor in pNET. Methods: In a retrospective single centre cohort study, we examined the influence of MetS in 120 patients with curative intended resection of pNETs on overall survival (OS), recurrence free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…As for the role of metformin, only five studies explored its role in the setting of pNET[ 17 , 27 , 29 , 32 , 37 ]. In detail, two studies reported the role of metformin in the insurgence of pNET[ 27 , 29 ], and the remaining three explored PFS, TFS, or OS[ 17 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the role of metformin, only five studies explored its role in the setting of pNET[ 17 , 27 , 29 , 32 , 37 ]. In detail, two studies reported the role of metformin in the insurgence of pNET[ 27 , 29 ], and the remaining three explored PFS, TFS, or OS[ 17 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, preceding studies indicated that co‐morbid metabolic syndrome potentially worsened clinical outcomes of cancer patients. 19 , 20 However, to date, data comparing the subsequent CVD risk between cancer patients with and without metabolic syndrome are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence was different depending on the cancer site, 17 metabolic syndrome was not a rare co‐morbidity among cancer survivors. Further, preceding studies indicated that co‐morbid metabolic syndrome potentially worsened clinical outcomes of cancer patients 19,20 . However, to date, data comparing the subsequent CVD risk between cancer patients with and without metabolic syndrome are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…MetS-Patienten haben aber nicht nur ein erhöhtes Krebsrisiko, sondern z. T. erkranken sie auch früher als Stoffwechselgesunde [16,17]. Das tumorspezifische 5-Jahres-Überleben von MetS-Patienten liegt unter dem von stoffwechselgesunden Tumorpatienten [18,19]. So geht das MetS mit einer bis 2,4-fach erhöhten Krebssterblichkeit einher [9,10,11].…”
Section: Hintergrundunclassified
“…Als zugrunde liegende Mechanismen werden insbesondere hormonelle und Wachstumsfaktoren (IGF-1, Insulin) angeschuldigt [64]. Bei Patienten mit resezierten, neuroendokrinen Pankreastumoren prognostiziert das MetS ein weniger günstiges Langzeit-Überleben [65]. Adenokarzinome der Speiseröhre und des Magens Das MetS erhöht das Risiko, an Adenokarzinomen der Speiseröhre, des ösophagogastralen Übergangs und der Magenkardia zu erkranken [66,67,68,69].…”
Section: Bauchspeicheldrüsenkrebsunclassified